2019
DOI: 10.1155/2019/2762978
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Different Components of Climate with Human Pituitary-Thyroid Axis and FT3/FT4 Ratio: A Study on Euthyroid and SCH Subjects in Two Different Seasons

Abstract: Background Various changes in thyroid hormones (TH) and thyroid-stimulating hormone (TSH) level were observed in different seasons among euthyroid and hypothyroid subjects living in areas with an extreme temperature difference between summer and winter. Objectives This study aims at finding the effect of temperate climate on the seasonal variations of TSH and TH in euthyroid and subclinical hypothyroidism (SCH) subjects and at evaluating if the test season has an effect on the number of subjects diagnosed as S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
(61 reference statements)
2
15
0
1
Order By: Relevance
“…In the longitudinal analysis of 181 subjects, no significant differences were detected in the thyroid parameters between summer and winter. Consistent with our observations, previous studies in healthy adults have shown that TSH levels decreases in summer-spring, while it increases in autumn-winter (6,7,15,(19)(20)(21)(22)(23)(24)(25). The seasonal variation of TSH between winter and summer reached an absolute difference of more than 10%-15% in a multinational study of Belgian, British, and Japanese residents (21).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the longitudinal analysis of 181 subjects, no significant differences were detected in the thyroid parameters between summer and winter. Consistent with our observations, previous studies in healthy adults have shown that TSH levels decreases in summer-spring, while it increases in autumn-winter (6,7,15,(19)(20)(21)(22)(23)(24)(25). The seasonal variation of TSH between winter and summer reached an absolute difference of more than 10%-15% in a multinational study of Belgian, British, and Japanese residents (21).…”
Section: Discussionsupporting
confidence: 91%
“…The monthly average temperatures range from -11.2°C in January to 24.6°C in July ( 14 ). Therefore, the distinct summer and winter climates in this region make Shenyang an appropriate location to investigate the effect of climatic variations on thyroid hormone levels in its population ( 15 ). In this study, “spring” was defined as being from March to May, “summer” from June to August, “autumn” from September to November, and “winter” from December to February.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, although the 10 (aged 32 to 66 years) ( 53 ) and 7 (aged 27 to 66 years) ( 54 ) primary hypothyroid patients in two longitudinal Japanese studies received constant doses of levothyroxine (L-T4), their unstimulated TSH levels and TSH levels after TRH stimulation were higher in winter compared to summer. In contrast, no significant difference was found in mean (SD) TSH levels measured in 25 subclinical hypothyroid patients with a mean (SD) age of 36.44 (14.82) years in winter [6.04 (1.17) mU/L] compared to summer [6.64 (1.60) mU/L] in Iraq ( 50 ).…”
Section: Sources Of Within-person Variation In Tsh Levelsmentioning
confidence: 86%
“…Likewise, no significant seasonal difference was present in a small subset of 159 subjects of this study in which TSH was measured twice in the same year ( 49 ). In 152 Iraqi euthyroid subjects with a mean (SD) age of 32.24 (12.05) years who had their TSH levels measured in both summer and winter seasons, no significant difference was found between summer [mean (SD) of 2.34 (1.25) mU/L] and winter [2.25 (1.25) mU/L] measurements ( 50 ). Andersen et al found 8% higher serum TSH concentrations in autumn and winter than in spring and summer using monthly blood samples in 15 healthy Danish men with an age range of 24–53 years, but this difference was not statistically significant ( 51 ).…”
Section: Sources Of Within-person Variation In Tsh Levelsmentioning
confidence: 99%
“…[39][40][41] We did not adjust for season because, to our knowledge, no evidence exists on the association of season of pregnancy with free T 4 or TSH levels (despite associations with air pollution). 42,43 Pregnant women who were included in the analysis were different from those excluded because of missing data on exposure and outcome (eTable 3 in the Supplement). To address the selective nonresponse arising from these differences, we used inverse probability weighting.…”
Section: Discussionmentioning
confidence: 99%